Dysphagia : clinical management in adults and children - Groher, Michael E.; Crary, Michael A., 1952-; ScienceDirect eBooks (St. Louis, Missouri : Elsevier, 2016)
Develop the understanding and clinical reasoning skills you'll need to confidently manage dysphagia in professional practice! This logically organized, evidence-based resource reflects the latest advancements in dysphagia in an approachable, student-friendly manner to help you master the clinical evaluation and diagnostic decision-making processes. Realistic case scenarios, detailed review questions, and up-to-date coverage of current testing procedures and issues in pediatric development prepare you for the conditions you'll face in the clinical setting and provide an unparalleled foundation.
Dysphagia unplugged -- Normal swallowing in adults -- Adult neurologic disorders -- Dysphagia and head/neck cancer -- Esophageal disorders -- Respiratory and iatrogenic disorders -- Clinical evaluation of adults -- Imaging swallowing examinations : videofluoroscopy and endoscopy -- Treatment considerations, options, and decisions -- Treatment for adults -- Ethical considerations -- Typical feeding and swallowing development in infants and children -- Disorders affecting feeding and swallowing in infants and children -- Evaluating feeding and swallowing in infants and children -- Treatment of feeding and swallowing difficulties in infants and children.
Print version record.
Includes index.
Elsevier
Keywords: Deglutition disorders; Esophagus -- Diseases; Ingestion disorders; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Deglutition disorders; Esophagus -- Diseases; Ingestion disorders; Deglutition Disorders; Electronic books